SOFTWARE EASY TO WORK LIBRARY EMPLOYEES IN SMAN 1 KOTA PAGAR ALAM WEB-BASED - Buhori Muslim (COMPUTING | Jurnal Informatika, 2022)
This research was conducted at the library of SMAN 1 Pagaralam City because there were problems at the time of borrowing, returning and checking book data and borrower data so that supporting software was needed so that services could be carried out quickly and data processing could be done accurately and could be done anytime where course by the officer or by the borrower of the book, then website-based software is built, this research uses web engineering development and methodology, and so that in the implementation of website development a quality software application model or system requirements specification is used, in the following order: formulation, analysis, planning, engineering, page generation, and evaluation. So that this research has produced software that can be used by library staff of SMAN 1 Pagaralam City when serving book borrowers and processing book data, so the performance of library staff is getting better.